Pancasila and Civic Education Learning by Non Pancasila and Civic Education Program Graduate - Elmas Dw Ainsyiyah; Andres M. Ginting (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to (1) find out planning and understanding of learning by Non Pancasila and Civic Education Program Graduate (2) to find out the learning done by Non Pancasila and Civic Education Program Graduate (3) In order to know the obstacles faced by Pancasila and Civic Education teachers by Non Pancasila and Civic Education Program Graduate. The research used in this case uses qualitative research methods through interview techniques with sources in which there are vice principals in the field of curriculum, the teacher concerned from the school under study. The results obtained in this study are, there are teachers who teach Pancasila and Civic Education are graduate Teacher of Pancasila and Civic Education Study Program, Sociologists, and there are Bachelor of Laws. The teacher also experiences many difficulties in delivering the material in class. Students are shaken up by boredom because the teacher's teaching style is monotonous with lectures and memorization, moreover Pancasila and Civic Education has memorized the constitution material which makes students lazy to follow the learning process. From the results of this research, schools must also have a role in equipping Non Pancasila and Civic Education Program Graduate with adequate learning resources so that teachers have thorough preparation before entering class. Teachers must also be able to overcome obstacles that occur in the classroom so that an interactive learning process occurs with students so that Pancasila and Civic Education subjects do not become a scourge for them.